Analysis of Factors Influencing The Selection of Location on The Success of Micro-Small Service Business in Around Campus Unitri Malang, East Java, Indonesia - Costa, Fidel da (International Journal of Management and Business, 2024)
This study aims to examine the effect of location selection on business success in small micro service businesses around the Unitri Malang Campus. Based on various literatures, many factors influence the choice of business location. However, location decisions often depend on the type of business, for retail and professional services businesses, the strategy used is focused on maximizing revenue. The main reason for the difference in location selection is the difference in the needs of each business. A good location is an individual matter when stated simply, "it all depends" on the needs of each business. This study uses data obtained directly from the field, namely through direct observation, interviews, and by giving questionnaires to the owners of small micro service businesses around the Unitri Malang Campus. The results of the study show that proximity to infrastructure, business environment, and location costs have a positive and significant effect on business success. Of the three independent variables, location costs are the variables that have the most influence compared to the other two variables. Therefore, in choosing a business location, business owners should pay more attention to the costs that must be incurred to get a business location.